Geographies of Medical and Health Humanities: A Cross-Disciplinary Conversation. Issue 2 (3rd July 2018) - de Leeuw, Sarah; Donovan, Courtney; Schafenacker, Nicole; Kearns, Robin; Neuwelt, Pat; Squier, Susan Merill; McGeachan, Cheryl; Parr, Hester; Frank, Arthur W.; Coyle, Lindsay-Ann; Atkinson, Sarah; El-Hadi, Nehal; et al.
Abstract : In recent years, both within and beyond academic and clinical spheres, medical and health humanities have become increasingly influential. Drawing from interdisciplinary fields in the humanities, social sciences, and the arts, medical and health humanities present unique lenses for considering nuanced spaces and lived experiences of health and health care; they also help challenge traditional ways that medicine and health care are understood and practiced. This collection brings together practitioners and theorists working broadly in medical health humanities, asking them both to consider their work as temporally and spatially located and to position their practices in conversation with a growing uptake of humanities methods and methodologies in other disciplines. The work of nine contributors uses these themes as a starting point for thinking about the future of medical health humanities in new and potentially even more productive ways.